Improving Students’ Vocabulary Achievement by Using the Web Game Skribbl.io at an Indonesian Junior High School in Jember - Mohamad Rahmad Ramdhani (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
In teaching English as a Foreign Language, many things must be covered to master the language. For example, when mastering listening, speaking, reading, and writing. However, the fundamental thing that needs to be learned is vocabulary. Wilkins (cited Thornbury, 2002) states that without grammar, very little can be conveyed, without vocabulary nothing can be conveyed. We can hardly communicate without grammar, and we cannot communicate without vocabulary. It is treated as fundamental knowledge in order to master other language skills. Improving vocabulary will eventually end the improvement of the language itself. Nowadays, teaching vocabulary has started to use technology in delivering the subjects, and gamified learning has gained much attention that is being used as a tool in teaching.
Reupload file repositori 09 Mar 2026_Maya
Keywords: Vocabulary Achievement